2009
DOI: 10.1590/s1982-56762009000300011
|View full text |Cite
|
Sign up to set email alerts
|

Tratamento químico de sementes de mamão visando ao controle de Rhizoctonia solani

Abstract: Parte da Dissertação de Mestrado da primeira autora. Universidade Estadual do Norte Fluminense. Campos dos Goytacazes RJ. 2007. RESUMOAvaliou-se a eficiência do tratamento de sementes de mamoeiro com fungicidas no controle de Rhizoctonia solani. Foram realizados dois experimentos nos quais as sementes foram tratadas com fungicidas nas seguintes doses (g i.a. kg -1 de sementes): triadimenol (0,5 e 1,0), pencycuron (1,0 e 2,0), thiabendazole (5,0 e 10,0), fludioxonil (0,25 e 0,50), difeconazole (1,0 e 2,0), capt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…However, in the first count test, the control gave the best result, together with Metalaxyl-M + Fludioxonil and Iprodione + Thiram, with no differences between them (p ≤ 0.05). As observed for germination, Captan also adversely affected seed vigor in both tests, corroborating with results from Campos et al (2009) for papaya seeds, where Captan also adversely affected seed vigor. There were no statistical differences between treatments for the electrical conductivity test in contrast to the results obtained by Nascimento and Cícero (1991) for pea seeds.…”
Section: Resultssupporting
confidence: 87%
“…However, in the first count test, the control gave the best result, together with Metalaxyl-M + Fludioxonil and Iprodione + Thiram, with no differences between them (p ≤ 0.05). As observed for germination, Captan also adversely affected seed vigor in both tests, corroborating with results from Campos et al (2009) for papaya seeds, where Captan also adversely affected seed vigor. There were no statistical differences between treatments for the electrical conductivity test in contrast to the results obtained by Nascimento and Cícero (1991) for pea seeds.…”
Section: Resultssupporting
confidence: 87%
“…suggested the use of captan for papaya seed protection and Posse (2005) reported that benomyl and the mixture (iprodione + benomyl) were effective in the control of papaya damping off. Campos et al (2009) evaluated ready-to-use formulations of the fungicides captan, tolylfluanid, thiabendazole, difeconazole, pencycuron and fludioxonil and concluded that they were not toxic to the seeds and seedlings of papaya at the tested concentrations.…”
Section: Introductionmentioning
confidence: 99%